Pengaruh Perbandingan Terigu dan Tepung Kacang Merah (Phaseolus vulgaris L) terhadap Karakteristik Kue Semprit - Aprissa Erina Putri, Wanda; Yusa, Ni Made; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 2 (2023): Jurnal ITEPA, 2023)
The use of wheat flour as a raw material in the making of Semprit cookies creates new problem, such as the high quantity of wheat flour is not comparable with the nutritional quality like fiber and protein. It is necessary to diversify food using flour from local commodities such as red bean flour in order to meet fiber and protein needs, and also to reduce wheat flour dependence. This research aimed to determine the effect of the comparison of wheat flour and red bean flour on the characteristics of semprit cookies and to find out the right comparison to produced a semprit cookies with the best characteristics. The experimental design used was a Completely Randomized Design (CRD) with a comparison of wheat flour and red bean flour consisting of 5 treatments, namely: 100%: 0%, 80%: 20%, 60%: 40%, 40%: 60%, and 20%:80%. All treatments was repeated 3 times so that 15 experimental units were obtained. The data obtained were analyzed by variance and if the treatment had a significant effect, it was continued with Duncan Multiple Range Test (DMRT). The results showed that the comparison of wheat flour and red bean flour had a significant effect on water content, ash content, protein content, fat content, carbohydrates content, crude fiber content, hedonic test for color, aroma, taste, texture, and overall acceptance, and scoring test for color and taste. Comparison of 60% wheat flour and 40% red bean flour had the best characteristics of with moisture content 7.17%, ash content 1.08%, protein content 11.10%, fat content 33.54%, carbohydrate content 51.89 %, crude fiber content 6.26%, color liked, aroma liked, taste liked, texture liked, overall acceptance liked, light brown color, and a slightly distinctive taste of red bean.